Climate Change Under the New International Order (The Role of Carbon Taxes in the Redistribution of International Powers) - Dalal Muhammad Ali (Zien Journals, 2023)
Global climate change has led to the necessity of concerted global efforts for a world free of carbon dioxide emissions, by imposing two processes: carbon taxes and carbon markets. It is not constrained by national borders according to the increased flexibility of movement in front of the base of income taxes and factors of production, and modern technology contributes to facilitating this task through the transfer of funds. From fossil fuels, their taxes are high, and these taxes can be benefited from with the help of the countries of the South to advance their economic, environmental, social and political realities, and strive to catch up with the developed countries by applying the taxation system, and the process is participatory for a carbon-free future and the possibility of reaching zero neutrality in the year 2100, in the manner in which Everyone can live in a safe and clean environment with future environmental sustainability
Keywords: Climate change; carbon taxes; carbon markets; New international order